Optimal Design of Heavy Vehicle Suspension System Subjected to Random Road Input - Gupta, Ashish; Tiwari, Sumit; Maurya, Nagendra (International Journal of Engineering and Technology, 2018)
Vehicle suspension system plays a vital role in diminishing the vibration caused by the road roughness and prevent it from transmitting to the driver and the passenger. In this paper conventional type suspension is used for process of optimization. The computational model of suspension is created through bond graph modeling. Further this model is simulated subjected to h1 and h2 type random road condition as suggested by ISO 8608. So that the performance can be done as real time inputs and typical Indian scenario. Optimized parameters of leaf spring is obtained through L9 modified orthogonal array generated by Taguchi method. These parameters are obtained for reducing the total stress by minimizing the signal to noise (Signal/Noise) ratio. Further, ANOVA is applied to determine the significant process parameters, which are mostly influencing the total stress and deflection of the spring.Â